Nanoselenium and Selenium Yeast Have Minimal Differences on Egg Production and Se Deposition in Laying Hens - Meng, Tian-Tian; Lin, Xue; Xie, Chun-Yan; He, Jian-Hua; Xiang, Yang-Kui; Huang, Yi-Qiang; Wu, Xin (Biological trace element research, 2021)
The objective of this study was to compare the effects of nanoselenium (NS) and selenium yeast (SY) on the performance, egg selenium (Se) concentration, and anti-oxidative capacity of hens. A total of 216 Brown Hy-line hens (29-week old) were randomly allocated into three treatments (6 replicate/treatment, 12 hens/replicate). The pre-trial period lasted 7 days, and the experimental period lasted 35 days. Dietary treatments included corn-soybean meal basal diet (containing 0.16 μg Se/g, as control group), and basal diet supplemented with 0.3 mg Se/kg diet (Se was from NS or SY), called as SY group or NS group, respectively. At the end of the experiment, one hen per replicate from each treatment was slaughtered. Liver, spleen, and kidney tissues were sampled for the determination of Se concentrations. The results showed that NS or SY supplement significantly improved feed conversion ratio ( P < 0.05), soft broken egg rate ( P < 0.05), and the serum T-AOC value ( P < 0.05) when compared with control group. Remarkably, the deposition of Se increased significantly ( P < 0.05) and equivalently in egg, liver, and kidney of hens supplemented with both NS and SY. Interestingly, SY supplement also enhanced the serum CAT and SOD activities ( P < 0.05), NS but not SY significantly reduced serum MDA ( P < 0.05), whereas RT-PCR results did not show significant differences in the mRNA levels of antioxidant genes among three groups ( P > 0.05). Taken together, dietary supplemented with SY or NS improved the Se deposition in eggs, liver and kidney of laying hens, increased antioxidant activity, and NS supplement had greater Se deposition in the kidney tissue than SY supplement. SY or NS supplement could be considered to be applied for Se-enriched egg production.